Urban Prevalence of Listeria spp. and Listeria monocytogenes in Public Lavatories and on Shoe Soles of Facility Patrons in the European Capital City Vienna. (21st April 2014) - Schoder, D.; Schmalwieser, A.; Szakmary‐Brändle, K.; Stessl, B.; Wagner, M.
Summary The aim of this study was to determine the prevalence of Listeria spp. and Listeria monocytogenes (L. monocytogenes) in urban public lavatories and on shoe soles of facility patrons in a European capital city. More than 91% of all municipal public lavatories in Vienna close to public hubs were included in this study. Overall, 373 swab samples of public lavatories and shoes of facility patrons were enriched, according to ISO 11290‐1. Listeria monocytogenes isolates were subtyped using pulsed‐field gel electrophoresis. A total of 24 samples were positive for Listeria spp., yielding an overall prevalence of 6.4% (24/373). Listeria monocytogenes was found in 2.1% (8/373) of all samples. Swabs from lavatories in parks, container lavatories and lavatories at markets had the highest prevalences of 20.7% (6/29), 20% (2/10) and 12.5% (1/8) Listeria spp., respectively. These detection rates were statistically significantly higher than those associated with lavatories in shopping centres (P = 0.003, P = 0.002, P = 0.02) and at public transport locations (P = 0.0004, P = 0.005, P = 0.02). Shoes sampled at Christmas markets showed the highest Listeria spp. and L. monocytogenes prevalences of 80% (4/5) and 40% (2/5), respectively. With regard to shoe type, Listeria spp. detection rates were 14.3% (3/21; winter boots), 13.3% (2/15; hiking boots), sport shoes (5.9%; 2/34) and brogues (5.1%; 4/79). No Listeria spp. were found on shoe soles that had smooth treads (0/76), while Listeria spp. were detected on 19.5% (8/41) of medium depth tread shoe types and on 9.4% (3/32) of deep tread shoes. These data suggest that soil environment is still one of the most important reservoirs for the foodborne pathogen L. monocytogenes.